Contenido de carbono de la biomasa arbórea en un sistema agroforestal tradicional en la finca experimental La Represa, perteneciente a la Universidad Técnica Estatal de Quevedo (UTEQ), cantón Quevedo, provincia de Los Ríos - Tovar Arboleda, Josué Joel (2021)
Currently, carbon capture plays an important role in climate change, it consists in eliminating excess carbon dioxide that is stored in the atmosphere and produces the so-called greenhouse effect. The main objective of the research was to determine the carbon content of the tree biomass in a traditional agroforestry system in the experimental farm La Represa, Quevedo canton, Los Ríos province. The sample units of the plots were established and the reference was placed in the center of each one, using a stake. The carbon content of the tree biomass was evaluated in a traditional agroforestry system, with the forest species T. grandis and T. cumingiana combined with Theobroma cacao. To obtain the results, data of dasometric variables such as DAP were collected, the application of equations was able to obtain the necessary data for the calculations of height and carbon emission. In height T. grandis presented an average of 19.73 m and T. cumungiana 18.15 m, in DBH T. grandis with 0.41 m, and T. cumungiana presented 0.26 m. in basal area T. grandis presented 0.132 m, and T. cumingiana 0.053 m. in volume T. grandis registered a volume of 1.82 m3 , and T. cumungiana a lower average of 0.67 m3. In biomass / ha T. grandis presented 0.14062 and T. cumungiana a value of 0.04376 was obtained. The carbon content of T. grandis obtained a better average of 0.000025089 per individual and T. cumingiana that registered 0.000010643 of carbon / individual. The amount of aerial biomass in which 60 trees were evaluated for T. grandis LF and 63 FOR T. cumingiana was determined, determining that T. grandisis the species with the highest amount of stored carbon because it presents an average of 0.00025089 CO2 / ha., Despite the fact that it presents a lower value for the number of trees. Key words: carbon, biomass, diameter, IMA